Pour un amorcement des pratiques numériques en classe de langue, entre réflexions théoriques et variations actionnelles - Sarah Azizi; Zineb Borhani (Multilinguales)
We are witnessing an upheaval in the designs and methods implemented within classes to adapt to the advent of technology, particularly in teaching. Modern didactics tends to debate this point in relation to the means offered by this device as well as its limits in educational practices. The assets that we can identify in this context are innumerable on a cognitive, socio-cultural and cultural level, but it remains a new orientation not yet well defined and woven with difficulties. In our humble work, we wanted to underline the importance of the integration of ICT particularly in the university context and the different modalities of their implementation as well as the obstacles observed in the field.